HIGHLY PROSPECTIVE OBJECT OF THE MINERAL AND RAW MATERIAL BASE OF UKRAINE. PART 2. NON-METALLIC MINERALS - MYKHAILOV, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
A brief description of highly prospective objects of the mineral-raw material base of non-metallic minerals of Ukraine is given. Based on an expert assessment of their investment attractiveness, the following types of raw materials were selected as the most prospective: kaolin (Zhezhelivske, Glukhovetske, Turbivske, Velikogadomynetske deposits); facing stones (Slipchytske and Golovinske deposits of labradorite; Omelyanivske, Tokivske, Kapustianske, Lyznitske and Kornynske deposits of granite); refractory clays (Chasiv-Yarske, Novoraiske, Volodymyrivske, Pologivske); graphite (Zavallivske, Burtynske (Khmelivska section) deposits); granate (Slobidske, Ivanivske); quartz raw materials (Husarivske, Velikohlibovitske); piezoquartz (Volynske); phosphorites (Zhvanske); limestones for the sugar industry (Zamok, Lysohirka); bentonite (Cherkaske deposit). Among the non-metallic minerals of Ukraine, these deposits have the highest level of investment attractiveness, the lowest investment risks, and can be recommended as priority objects for investment in their study and industrial development. To determine the investment prospects of concrete objects, a preliminary geological and economic assessment of the feasibility and profitability of their industrial development is necessary.
Keywords: mineral raw material base; deposit; non-metallic minerals; investment attractiveness